Ethnomathematics study: cultural values and geometric concepts in the traditional “tanean-lanjang” house in Madura - Indonesia - Sari, Ariesta Kartika; Budiarto, Mega Teguh; Ekawati, Rooselyna (Lembaga Pengembangan Publikasi Ilmiah dan Buku Ajar, Universitas Muhammadiyah Surakarta, 2022)
One of the cultural outcomes of the Madurese community is the traditional tanean lanjang house with a long front yard, designed from several batih (nuclear) families, consisting of a married couple with unmarried children. This study explores geometric concepts of the traditional house to demonstrate how they can be useful for learning mathematics. The descriptive qualitative study described the mathematical concepts found in the tanean lanjang traditional house or settlement in Madura. Furthermore, an ethnographic method was also used to analyze documents, ethnographic notes, and documentation (photos). Data analysis techniques employed an interactive model of data collection, data reduction, data presentation, and conclusion. The results of the study show that the cultural values and geometric concepts of the tanean lanjang traditional house comprised (1) kinship and brotherhood values, (2) harmony in the household, and (3) strength in the household. The geometric concepts contained in the traditional tanean lanjang house include 2-dimensional shape (i.e., rectangle, trapezoid, triangle), perimeter of 2-dimensional shape, area of 2-dimensional shape, 3- dimensional shape (i.e., triangular prism), the volume of 3-dimensional shape, curve, and the concept of reflection in geometry.